2014
DOI: 10.1111/dgd.12135
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric inheritance of Cyclin D2 maintains proliferative neural stem/progenitor cells: A critical event in brain development and evolution

Abstract: JapanAsymmetric cell division and cell cycle regulation are fundamental mechanisms of mammalian brain development and evolution. Cyclin D2, a positive regulator of G1 progression, shows a unique localization within radial glial (RG) cells (i.e., the neural progenitor in the developing neocortex). Cyclin D2 accumulates at the very basal tip of the RG cell (i.e., the basal endfoot) via a unique cis-regulatory sequence found in the 3 0 untranslated region (3 0 UTR) of its mRNA. During RG division, Cyclin D2 prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 87 publications
0
29
0
Order By: Relevance
“…Given the ability of progenitor cells to proliferate as well, we found that many proliferative neuron-restricted progenitors were accompanied by fewer proliferative NSCs in neurospheres derived from sNSCs than from cNSCs. Additionally, the time required for the development of the cerebral cortex is markedly long compared with spinal cord development [38,39], and E12.5 is the time for the cerebral cortex to generate a large pool of NSCs for further expansion [14,40,41]. On the other hand, sNSCs presented in this study are committed to the production of progenitor cells.…”
Section: Discussionmentioning
confidence: 83%
“…Given the ability of progenitor cells to proliferate as well, we found that many proliferative neuron-restricted progenitors were accompanied by fewer proliferative NSCs in neurospheres derived from sNSCs than from cNSCs. Additionally, the time required for the development of the cerebral cortex is markedly long compared with spinal cord development [38,39], and E12.5 is the time for the cerebral cortex to generate a large pool of NSCs for further expansion [14,40,41]. On the other hand, sNSCs presented in this study are committed to the production of progenitor cells.…”
Section: Discussionmentioning
confidence: 83%
“…During development, local synthesis of cytoskeletal and signaling molecules would be particularly advantageous as the cortex undergoes radial expansion [46], necessitating remodeling and growth of RGC endfeet. Local translation of fate determinants also could impact progenitor symmetric and asymmetric divisions and specify distinct neuronal sub-types [18, 47]. Indeed, we discovered endfoot transcripts encoding nuclear factors, which could function locally or shuttle back to the cell body, as has been observed in neuronal axons [48, 49].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cyclin D2 is asymmetrically distributed in daughter cells produced by radial glia cell proliferation in the developing cortex and has a role in G1/S progression. The daughter cell that receives Cyclin D2 maintains its radial glia proliferative state, whereas the other cell undergoes differentiation (reviewed in [44]). Finally, there is evidence that Cyclin D2 is required for the transition from radial glia to intermediate progenitor cells and has a role in proliferation and expansion of the intermediate progenitor pool [45].…”
Section: Discussionmentioning
confidence: 99%